CORAL LIFEFORM STRUCTURE IN SELECTED MARINE PROTECTED AREAS IN SOUTHERN CEBU - Piquero, Alfonso S.; Delan, Gloria G.; Rica, Rachel Luz V.; Corrales, Christine M.; Monte, Irene A. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 16 No. 1, 2013, 2018)
Marine protected area or marine reserve was first conducted in Central Visayas in 1974 as a tool to manage coral reef. It was then replicated throughout the Philippines.     The marine reserve of the following; Casay of Argao, Cawayan of Dalaguete, Daan-Lungsod Guiwang of Alcoy, North Granada of Boljoon and Sta. Cruz of Ronda has been established between the year 2000 to 2007. These MPAs were assessed to gather baseline information on its coral lifeform structure. Point-intercept transect (PIT) method was used in the observation. Benthic life form and reef substrate at each 0.25m point interval were identified and recorded along 50 meters transect line both inside and outside of these MPA’s. It has been observed that massive, branching and digitate form of corals dominated among the five sanctuaries. Percentage of Live Hard Corals were much higher inside than outside to all sanctuaries. Common to all these sanctuaries were noticeable presence of Dead corals with algae and coral rubbles indicating its exploitation. Casay, Cawayan and Daan-Lungsod MPAs had some Crown of thorn starfish which may pose threat to its coral community. It has been recommended that there should be strict implementation of rules among the Local Government Unit; more policing and a long term monitoring to continuously conserve and protect coral reef.